Preparation of hydrogen from metals and water without CO2 emissions. (9th November 2022) - Tan, Yuhua; Yang, Haitao; Cheng, Jiaxin; Hu, Jiacheng; Tian, Guocai; Yu, Xiaohua
Abstract: Considering the high calorific value and low-carbon characteristics of hydrogen energy, it will play an important role in replacing fossil energy sources. The production of hydrogen from renewable energy sources for electricity generation and electrolysis of water is an important process to obtain green hydrogen compared with classic low-carbon hydrogen production methods. However, the challenges in this process include the high cost of liquefied hydrogen and the difficulty of storing hydrogen on a large scale. In this paper, we propose a new route for hydrogen storage in metals, namely, electricity generation from renewable energy sources, electrolysis to obtain metals, and subsequent hydrogen production from metals and water. Metal monomers facilitate large-scale and long-term storage and transportation, and metals can be used as large-scale hydrogen storage carriers in the future. In this technical route, the reaction between metal and water for hydrogen production is an important link. In this paper, we systematically summarize the research progress, development trend, and challenges in the field of metal to hydrogen production. This study aim to aid in the development of this field. Highlights: A new route for hydrogen storage and production via metals on a large scale is proposed. Electrolysis to obtain metals by green electricity, and subsequent hydrogen production from metals and water. Metal monomers facilitate large-scale and long-term storage and transportation. Metals can be used as large-scale hydrogen storage carriers in the future. Metal-water hydrogen production can make full use of renewable energy without carbon dioxide.